ISOLASI DAN IDENTIFIKASI SENYAWA FLAVONOID DARI EKSTRAK ETANOL BUAH BELIMBING WULUH (Averrhoa bilimbi L.) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Siti Hamdanah; Syariful Anam; Jamaluddin Jamaluddin (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2015)
Star fruits (Averrhoa bilimbi L.) from family of oxalidaceae is a plant which has potential as an antibacterial Staphylococcus aureus and Escherichia coli. Flavonoid are the active compounds from the extract of star fruit which has potential as an antibacterial. Star fruit were extracting by ethanol 96 % using maceration. Extract were identified using thin layer chromatography (TLC) with eluent analytic n-butanol- glacial acetic acid- water (6:1:3). Preparative isolation using thin layer chromatography resulting three bands. Each band was centrifuged to obtain isolates. Physics isolates were analyzing using spectrophotometer UV Vis and chemically using color test (shift reagent). UV Vis spectrum results with shift reagent from isolates 1, suspected as isoflavone compound with OH groups in position 6,7,4 and OH groups in O- ring A, in isolates 2 was not flavonoid compound and predicted as other polyphenolic compound and in isolates 3 suspected of flavone compound with OH groups in position 5,6,7 and OH groups in O-ring A